ELABORAÇÃO DE UM PLANO PARA INSTALAÇÃO DA TURBINA A GÁS SOLAR TAURUS 60 (Revista Interdisciplinar Pensamento Científico, 2021)
The installation of industrial rotating equipments is extremely important, since it is a determinant factor, in combination with an adequate maintenance planning, for machine availability and reliability. The gas turbine is a rotating equipment which is extensively used in power generation area. The installation of gas turbine requires a strictly executed procedure because the equipment’s availability affects directly in production. This article aims to identify and analyze activities that make up the installation process of Solar Taurus 60 gas turbine. Methodology used for preparing this article consists of field research and bibliographic searches carried out in Google Scholar and Scielo websites to find articles and bibliographic reviews in Portuguese and English, with no restriction of publication date. The field research was performed in a company located in Macaé, in the countryside of Rio de Janeiro state, whose plant has nine gas turbines. Twelve steps have to be followed for the of Solar Taurus 60 gas turbine installation to be concluded. Boroscopy and alignment processes, extremely delicate steps, are included in this process. The installed turbine presents acceptable levels of reliability and availability when installed according to procedures presented in this work
Keywords: Gas turbine; Installation; Reliability; Availability.